Link between the North Atlantic Oscillation and the surface mass balance components of the Greenland Ice Sheet under preindustrial and last interglacial climates: a study with a coupled global circulation model - S. Ramos Buarque; D. Salas y Melia (Climate of the Past, 2018)
The relationship between the surface mass balance (SMB) components (accumulation and melting) of the Greenland Ice Sheet (GrIS) and the North Atlantic Oscillation (NAO) is examined from numerical simulations performed with a new atmospheric stretched grid configuration of the Centre National de Recherches Météorologiques Coupled Model (CNRM-CM) version 5.2 under three periods: preindustrial climate, a warm phase (early Eemian, 130 ka BP) and a cool phase (late Eemian, 115 ka BP) of the last interglacial. The horizontal grid of the atmospheric component of CNRM-CM5.2 is stretched from the tilted pole on Baffin Bay (72° N, 65° W) in order to obtain a higher spatial resolution on Greenland. The correlation between simulated SMB anomalies averaged over Greenland and the NAO index is weak in winter and significant in summer (about 0.6 for the three periods). In summer, spatial correlations between the NAO index and SMB components display different patterns from one period to another. These differences are analyzed in terms of the respective influence of the positive and negative phases of the NAO on accumulation and melting. Accumulation in south Greenland is significantly correlated with the positive (negative) phase of the NAO in a warm (cold) climate. Under preindustrial and 115 ka BP climates, melting along the margins is more correlated with the positive phase of the NAO than with its negative phase, whereas at 130 ka BP it is more correlated with the negative phase of the NAO in north and northeast Greenland.